ILMU MUNASABAH AL-QUR’AN - Ahmadiy Ahmadiy (LP3M Universitas Sains Al Qur'an, 2018)
Munâsabah's knowledge (knowledge about relevance among oneletter or sentence with letter or other sentence) form a part of Ulumal Qur ’ an. This knowledge its enough position urgent in order tomakes entirely al Qur's sentence ’ an as one whole unity (holistik).As it were observable in one of Ibn Katsir's interpretation method; al Qur ’ an yufassirû ba ’ dhuhu ba ’ dhan , the one sentence position isconjugate sentence another one, therefore understands al Qur ’ anshall whole, otherwise, therefore will come in deep modelinterpretation which atomistik (rashers).